MATERNAL SERUM LEVELS OF ADIPONECTIN IN PREECLAMPSIA - Khosrowbeygi, Ali; Ahmadvand, Hassan (Journal of Ayub Medical College Abbottabad, 2009)
Background: The results of the serum levels of adiponectin in preeclamptic patients are conflicting. Objective: The aim of the present study was to assess serum levels of adiponectin in women with preeclampsia compared with healthy pregnant women. Methods: A cross-sectional study was designed. The case group consisted of women with preeclampsia (n=30). The control group consisted of 30 matched normal pregnant women. Serum levels of adiponectin were assessed using enzyme-linked immunosorbent assay method. Results: Serum levels of adiponectin were significantly higher in the preeclamptic group than those in the normal control group. In the preeclamptic patients serum levels of adiponectin showed a significant negative correlation with body mass index while no correlation was found in the normal pregnant women. In women with preeclampsia, levels of adiponectin were decreased significantly in the overweight women compared with normal weight women, while in the control group no significant difference was observed. Conclusion: In conclusion, elevation of adiponectin levels might be a physiological feedback response to minimize endothelial dysfunction in preeclamptic patients. Keywords: Serum, Adiponectin, Preeclampsia, Pregnancy, BMI, ELISA.